No improvement of survival with reduced- versus high-intensity conditioning for allogeneic stem cell transplants in Ewing tumor patients - Thiel, Uwe; Wawer, A.; Wolf, P.; Badoglio, M.; Santucci, A.; Klingebiel, T.; Basu, O.; Borkhardt, A.; Laws, H. -J.; Kodera, Y.; Yoshimi, A.; Peters, C.; et al. (Annals of oncology, 2011)
Background - Outcomes of Ewing tumor (ET) patients treated with allogeneic stem cell transplantation (allo-SCT) were compared regarding the use of reduced-intensity conditioning (RIC) and high-intensity conditioning (HIC) regimens as well as human leukocyte antigen (HLA)-matched and HLA-mismatched grafts. - Patients and methods - We retrospectively analyzed data of 87 ET patients from the European Group for Blood and Marrow Transplantation, Pediatric Registry for Stem Cell Transplantations, Asia Pacific Blood and Marrow Transplantation and MetaEICESS registries treated with allo-SCT. Fifty patients received RIC (group A) and 37 patients received HIC (group B). Twenty-four patients received HLA-mismatched grafts and 63 received HLA-matched grafts. - Results - Median overall survival was 7.9 months [±1.24, 95% confidence interval (CI) 5.44-10.31] for group A and 4.4 months (±1.06, 95% CI 2.29-6.43) for group B patients (P = 1.3). Death of complications (DOC) occurred in 4 of 50 (0.08) and death of disease (DOD) in 33 of 50 (0.66) group A and in 16 of 37 (0.43) and 17 of 37 (0.46) group B patients, respectively. DOC incidence was decreased (P < 0.01) and DOD/relapse increased (P < 0.01) in group A compared with group B. HLA mismatch was not generally associated with graft-versus-Ewing tumor effect (GvETE). - Conclusions - There was no improvement of survival with RIC compared with HIC due to increased DOD/relapse incidence after RIC despite less DOC incidence. This implicates general absence of a clinically relevant GvETE with current protocols.
Gesehen am 02.11.2022
Erstmals online zugänglich: 6. Januar 2020, Version des Datensatzes: 6 Januar 2020